A photoacoustic imaging method for in-situ monitoring of laser assisted ceramic additive manufacturing. (July 2019) - Cheng, Baokai; Lei, Jincheng; Xiao, Hai
Highlights: Novel photoacoustic imaging technique for laser assisted additive manufacturing is proposed. Proof-of-concept experiments are performed and PA images are obtained. Only a microphone is needed as additional hardware, the cost is low for this method. Abstract: We propose an in-situ monitoring method of laser assisted ceramic additive manufacturing (AM) fabrication process using photoacoustic (PA) imaging technique. This method is potentially very practical and of low cost, as it can be easily implemented with little modification to the original AM system. A major advantage of this method is that it does not require any complex or expensive component to be installed, just need a microphone to be setup near the work-piece and a data processing program to analyse the acoustic data. By collecting the photoacoustic wave that produced by the laser scanning during the AM process, a spectrogram of the acoustic signal can be generated using short-time Fourier transform (STFT). The PA signal can be extracted by specifying the modulation frequency of the laser in the spectrogram. Combining with the scanning position of the laser beam, the PA image of the layer under processing can be obtained. Detection of two kinds of defects (metal defect and dried paste defect) have been demonstrated. Although there are many other kinds of possible defects in additive manufacturing processes, this method could be a practical and low cost way to monitor most of them with proper choice of parameters of the laser and detection system. The parameters of the system that can influence the PA image quality have also been discussed.